A case of constrictive pericarditis in an infant treated by radical pericardiectomy - Alp, Mete; Özme, Şencan; Sarıoğlu, Tayyar; Özdemir, Aytekin; Gökgöz, Levent; Akçevin, Atıf; Yurdakul, Yurdakul; Aytaç, Aydın (The Turkish Journal of Pediatrics, 1985)
A four-month-old boy with constrictive pericarditis, which is unusual in infancy, is presented. A radical pericardiectomy was performed on the patient. It is of interest that pathological examination of the resected pericardium revealed the presence of tuberculous pericarditis with fibrinous pericarditis, this was probably secondary to acute purulent staphylococcal pericarditis.
Keywords: constrictive pericarditis; infant; pericardiectomy; tubular pericarditis